The Cost of Exposing Large Institutional Orders to Electronic Liquidity Providers - Battalio, Robert; Hatch, Brian; Sağlam, Mehmet (Management Science, 2024)
We use a novel data set to examine the impact of exposing institutional orders to electronic liquidity providers (ELPs). We present empirical evidence that marketable pieces of large parent orders are routed to ELPs seemingly to avoid paying liquidity fees on exchanges. This routing decision results in lower net effective spreads for these child orders but leads to higher execution shortfall for the parent order. We provide evidence suggestive of a causal relation by utilizing the parent orders of investors that disallow the broker to route their child orders to ELPs. Our analysis suggests that ELPs detect the presence of the parent order very quickly given the transparent bilateral relation with the broker. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4871 .